2014
DOI: 10.5338/kjea.2014.33.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of Heavy Metals Induced by Bioaugmentation of a Phosphate Solubilizing Bacterium

Abstract: BACKGROUND:Excessive metals in the soil have become one of the most significant environmental problems. Phytoremediation has received considerable attention as a method for restoring the contaminated soils. The microbes having remarkable metal tolerance and plant growth-promoting abilities could also play a significant role in remediation of metal-contaminated soils, because bioaugmentation with such microbes could promote phytoextraction of metals. Therefore, the present study was focused on evaluating the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…This increase in plant growth by CPSB21 under Cr 6+ stress in soil may be attributed to its ability to produce siderophores, IAA, NH 3 , HCN, and P solubilization 24 . Similar to our results, bacterial mediated plant growth in sunflower and tomato under stress conditions has been reported 25 , 26 . Moreover, the inoculation of CPSB21 enhanced the chlorophyll content in both the plants.…”
Section: Discussionsupporting
confidence: 93%
“…This increase in plant growth by CPSB21 under Cr 6+ stress in soil may be attributed to its ability to produce siderophores, IAA, NH 3 , HCN, and P solubilization 24 . Similar to our results, bacterial mediated plant growth in sunflower and tomato under stress conditions has been reported 25 , 26 . Moreover, the inoculation of CPSB21 enhanced the chlorophyll content in both the plants.…”
Section: Discussionsupporting
confidence: 93%
“…Moreira et al (2016b) reported reduced Zn availability in the rhizosphere of maize inoculated with PGPB. Conversely, bioaugmentation-induced increases of TE availability in rhizosphere soils have also been reported (Sheng et al, 2012;Prapagdee et al, 2013;Arunakumara et al, 2014;Walpola et al, 2014;Babu et al, 2015;Gupta et al, 2018), which can be related to the secretion of siderophores by PGPB that bind TE enhancing their bioavailability and plant uptake (Rajkumar et al, 2010).…”
Section: Pgpbmentioning
confidence: 99%